A cutaneous Anthrax outbreak in Koraput District of Odisha-India 2015 - Priyakanta Nayak; Samir V. Sodha; Kayla F. Laserson; Arun K. Padhi; Basanta K. Swain; Shaikh S. Hossain; Aakash Shrivastava; Pradeep Khasnobis; Srinivas R. Venkatesh; Bikash Patnaik; Kailash C. Dash (BMC, 2019)
Abstract Background Cutaneous anthrax in humans is associated with exposure to infected animals or animal products and has a case fatality rate of up to 20% if untreated. During May to June 2015, an outbreak of cutaneous anthrax was reported in Koraput district of Odisha, India, an area endemic for anthrax. We investigated the outbreak to identify risk factors and recommend control measures. Method We defined a cutaneous anthrax case as skin lesions (e.g., papule, vesicle or eschar) in a person residing in Koraput district with illness onset between February 1 and July 15, 2015. We established active surveillance through a house to house survey to ascertain additional cases and conducted a 1:2 unmatched case control study to identify modifiable risk factors. In case control study, we included cases with illness onset between May 1 and July 15, 2015. We defined controls as neighbours of case without skin lesions since last 3 months. Ulcer exudates and rolled over swabs from wounds were processed in Gram stain in the Koraput district headquarter hospital laboratory. Result We identified 81 cases (89% male; median age 38 years [range 5-75 years]) including 3 deaths (case fatality rate = 4%). Among 37 cases and 74 controls, illness was significantly associated with eating meat of ill cattle (OR: 14.5, 95% CI: 1.4-85.7) and with close handling of carcasses of ill animals such as burying, skinning, or chopping (OR: 342, 95% CI: 40.5-1901.8). Among 20 wound specimens collected, seven showed spore-forming, gram positive bacilli, with bamboo stick appearance suggestive of Bacillus anthracis. Conclusion Our investigation revealed significant associations between eating and handling of ill animals and presence of anthrax-like organisms in lesions. We immediately initiated livestock vaccination in the area, educated the community on safe handling practices and recommended continued regular anthrax animal vaccinations to prevent future outbreaks.